Creative DNA The Royal Ballet's Christopher Newton talks - McCarthy, Brendan (Dance Books Ltd., Alton,Hampshire (UK), 2006)
The Royal Ballet's Christopher Newton a profile. PALABRAS CLAVE: Christopher Newton, Royal Ballet.